Assessment of Reactive-Powder-Concrete Strength Using Waste BrickSand Subjected to Internal and External Curing Conditions (Journal of Engineering, 2025)
The discarded construction waste materials can be re-used as a new source of aggregate. These wastes, such as clay bricks, can be managed by recycling them into new construction materials after being collected, dried, crushed, and ground for use in concrete production. This study aims to investigate the feasibility of using recycled brick waste as sand to produce sustainable reactive-powder-concrete (R-P-C), and to assess the influence of various curing techniques on its mechanical strength. In this study, two sustainable R-P-C mixtures (BM15 and BM30) were prepared, containing 15% and 30% brick waste as sand (BS), as a volume replacement for Sika sand in the reference mixture (RM). The mixtures were cured under three curing techniques: coating (C), high temperature + normal curing (HN) with three cycles: 1 day (HN1), 2 days (HN2), and 3 days (HN3) of immersion in (50 ± 2)°C water plus normal curing until the age of testing, and autogenous + normal curing  (AN), in addition to normal curing (N) as a control curing technique. The results indicated that the high temperature + normal curing was the most effective curing method for all mixtures, with improvements of 16.03%, 17.45%, and 18.53% for HN1, HN2, and HN3, respectively, in compressive strength at 28 days for RM. Additionally, results showed that sustainable R-P-C mixtures exhibited higher compressive strength than RM, with improvements up to 15.39% at 28 days, accompanied by proportional improvements in splitting tensile and flexural strengths for all mixtures under all curing regimes. These findings indicate that recycled brick as sand, when combined with proper curing, can produce sustainable R-P-C mixtures with high mechanical strength.